College Students' Reactions to Participating in Relational Trauma Research: A Mixed Methodological Study. Issue 21 (November 2017) - Edwards, Katie M.; Neal, Angela M.; Dardis, Christina M.; Kelley, Erika L.; Gidycz, Christine A.; Ellis, Gary
Using a mixed methodology, the present study compared men's and women's perceived benefits and emotional reactions with participating in research that inquired about child maltreatment and intimate partner violence (IPV) victimization and perpetration. Participants consisted of 703 college students (357 women, 346 men), ages 18 to 25 who reported on their childhood maltreatment, adolescent and adult IPV victimization and perpetration, and their reactions (perceived benefits and emotional effects) to participating. Participants' reactions to participating were assessed using quantitative scales, as well as open-ended written responses that were content coded by researchers. Women reported more personal benefits from research, whereas men and women reported similar levels of emotional reactions to research participation. Furthermore, greater frequencies of child maltreatment and IPV victimization were related to higher levels of emotional reactions. Common self-identified reasons for emotional reactions (e.g., not liking to think about abuse in general, personal victimization experiences) and benefits (e.g., reflection and awareness about oneself, learning about IPV) were also presented and analyzed. These data underscore the importance of future research that examines the behavioral impact of research participation utilizing longitudinal and in-depth qualitative methodologies. Findings also highlight the potential psychoeducational value of research on understanding the reasons underlying participants' benefits and emotional effects.